Kajian Analisi Hubungan Kondisi Fisik Rumah Resiko Peceraian Terhadap Penderita TB Paru Di Rungan Perawatan TB Paru Rsud Arifin Achmad Pekanbaru - Chairil (LPPM Universitas Muhammadiyah Riau, 2019)
Pulmonary tuberculosis (pulmonary tuberculosis) is the third cause of death after cardiovascular and respiratory tract diseases. The factors that cause pulmonary tuberculosis include low income, economically low nutritional quality of the community, poor physical condition of the house (including air quality in the house), as well as the risk of divorce from pulmonary tuberculosis patients. This study aims to determine the relationship of physical risk conditions of the house. Pulmonary TB patients Population and sample of this study 80 respondents in June 3 to August 2018 with the sample ascentental method. As a result of this study there is a relationship between the physical condition of the house with Pulmonary TB that there is a significant relationship between Physical House with Patients with Pulmonary TB. This is evidenced by the value of P - value> 0.05 which is 1.120 with OR: 0.346 and 85% CI: 0.075 - 1.409. And for the risk of divorce with pulmonary tuberculosis there is no meaningful relationship between divorce and patients with pulmonary TB. This is evidenced by the P value - value> 0.05 which is 0.120 with OR: 0.326 and 95% CI: 0.075 - 1.409. Conclusion This paper is a physical home code such as occupancy density, ventilation and kitchen room temperature can be the occurrence of pulmonary Tb so recommended to improve the condition of the house and treatment of patients as early as possible until the patient is cured and for the risk of divorce there is no relationship with pulmonary tuberculosis the couple accept the state of being, but the need for promotional measures to provide a picture of a healthy home condition and divorce is not a solution for TB sufferers Lungs. Keywords: pulmonary tuberculosis, state of the home condition, risk of divorce